Structure Design Evaluation of Muhammadiyah Banjarmasin University Convention Centre Building Due to Functional Change Based on SNI 03-2847-2019 - Anggarini, Elia; Muzaidi, Irwandy (Universitas Muhammadiyah Yogyakarta, 2023)
The Muhammadiyah Banjarmasin University Convention Centre Building was originally built as a guesthouse, over time it changed its function to become a place for lecture activities. Therefore, an evaluation of the initial structural design is carried out on the reliability of the building structure as regulated in Government Regulations in Permen PU No. 25 of 2007 concerning Certificate of Building Functioning or SLF. The data used in this study are primary and secondary data, where primary data is in the form of field tests to determine the uniformity of concrete quality, namely the bounce test using the Hammer Test tool on the beams and columns of the 1st floor and 2nd floor as many as 10 points, while secondary data uses preliminary planning data. Modeling is done in 3D using SAP2000 software. The results of research on the value of uniformity of concrete quality show mixed results, this is due to several factors, one of which is different casting methods in the field. Meanwhile, from the results of the analysis of the service ability of the building structure, the value of the Ultimate Moment (Mu) and Ultimate Load (Pu) as well as the Maximum Ultimate Moment (Mr) and Maximum Ultimate Load (Pr) is still able to withstand the loads acting on the structure even though it has changed its function based on SNI 03-2847-2019.